2020
DOI: 10.1055/a-1222-9067
|View full text |Cite
|
Sign up to set email alerts
|

Psychisches Befinden in der Bevölkerung während der COVID-19-Pandemie

Abstract: Zusammenfassung Ziel der Studie Zusammenhangsanalyse von wahrgenommenen Alltagsbelastungen während der COVID-19-Krise und Persönlichkeitsaspekten mit dem aktuellen psychischen Befinden in der Bevölkerung sowie Vergleich der psychischen Symptomatik mit einem Survey von 2018. Methodik Zufallsstichprobe aus der Bevölkerung (n = 721), die zu coronabezogenen Einschätzungen, Persönlichkeitsaspekten und aktuellem psychischen Befinden (WHO-5, PHQ-D) schriftlich befragt wurde. Ergebnisse A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
3
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
3
11
3
10
Order By: Relevance
“…In contrast, this study found slightly increased psychological distress (anxiety and depression) but was confined to the first weeks of lockdown in Germany (late March to early April 2020, as published so far [ 7 ]). Another German study with population-based pre-pandemic reference data did not identify general differences in mental health conditions according to the WHO-5 well-being index and PHQ-D between 2018 and 2020 (late April to late May) [ 39 ]. Compared to these longitudinal data from the general population, patients with current psychiatric conditions in the present study showed higher baseline levels of symptoms before the pandemic but seemed to experience a stress response very similar to that of general population samples: The initial rise of psychosocial burden was followed by a decline, possibly reflecting adaption.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this study found slightly increased psychological distress (anxiety and depression) but was confined to the first weeks of lockdown in Germany (late March to early April 2020, as published so far [ 7 ]). Another German study with population-based pre-pandemic reference data did not identify general differences in mental health conditions according to the WHO-5 well-being index and PHQ-D between 2018 and 2020 (late April to late May) [ 39 ]. Compared to these longitudinal data from the general population, patients with current psychiatric conditions in the present study showed higher baseline levels of symptoms before the pandemic but seemed to experience a stress response very similar to that of general population samples: The initial rise of psychosocial burden was followed by a decline, possibly reflecting adaption.…”
Section: Discussionmentioning
confidence: 99%
“…One can predict that these problems will continue to worsen as more lockdowns are being implemented. Emotional and behavioural problems that previously affected just under a fifth of all children and adolescents now occur in just under a third [ 9 ]. Counselling centres, outpatient clinics and clinics report noticeable increases in anxiety disorders, depression, suicidality and eating disorders.…”
Section: Reflecting On the Past Year What Can We Learn?mentioning
confidence: 99%
“…In einer repräsentativen Zufallsstichprobe der Mannheimer Bevölkerung, in der das aktuelle psychische Befinden (WHO‑5, Patient Health Questionnaire [PHQ-D]) im Zeitraum vom 24.04. bis 23.05.2020 erhoben und mit Ergebnissen aus einer Befragung aus dem Jahr 2018 verglichen wurde, ergaben sich zwar bezüglich der Mittelwerte des WHO-Summenwerts und der quantitativen Syndromkriterien im PHQ‑D keine signifikanten Unterschiede. Eine differenzierte Analyse zeigte jedoch, dass das psychische Befinden bei jüngeren Personen schlechter war und den persönlichen Resilienzfaktoren eine große Bedeutung zukommt [ 12 ]. Neben diesen die Versorgungssysteme schon jetzt belastenden akuten Folgeerscheinungen der Pandemie werden zunehmend auch kognitive Defizite als Kurz- und Langzeitfolgen der COVID-19-Infektion beschrieben.…”
Section: Hintergrundunclassified